COVID-19 evidence for athletes service (Aspetar, 2020)
Aspetar provides evidence-based information and guidance on the COVID-19 pandemic to athletes and those involved in athlete (health) care. Athletes Service Overview and Aim Athlete Questions Education Material Scientific Papers Important Resources Athletes` stories Repository of Local and International News (relevant to athletes and the COVID-19 pandemic)